(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this paper, ZnTe and ZnTe: mn films were obtained by laser deposition using ZnTe and mn co-deposition method. 2Te was used as targets and the ratio of shots was varied to obtain pure ZnTe films and films with 2% mn.ZnTe films were deposited with mn manganese for the purpose of p-type carrier concentration and to prove the effect of manganese concentration on the structural and optical properties of ZnTe thin films to consider their potential applications in electronic devices. After structural investigations conducted by X-ray diffraction technique, the studied samples are polycrystalline and have a cubic shape with preferred orientation along (111). XRD patterns were used to determine the microscopic parameters (crystal size, lattice modulus). Atomic force microscopy (AFM) was used to study the surface roughness of the thin films.A UV-Vis spectrophotometer was used to determine the energy gap.